Tecnologias sociais e práticas educativas contextualizadas para a convivência com o semiárido: partilhando saberes e construindo novos olhares em territórios camponeses - Araújo, Irenaldo Pereira de (2016)
The present study was created with the objective to research contextualized educational practices in peasant territories and their new perspectives on the constructive implications of the Brazilian semi-arid, which are realized through formative events that occur through the implementation process by Programa Um Milhão de Cisternas (P1MC), Programa Uma Terra e Duas Águas (P1+2) and Programa Cisternas nas Escolas (PCE) by social organizations that are part of the Articulação Semiárido Brasileiro (ASA. The ways these educational practices have contributed to the acquisition of new perspectives on the Brazilian Semi-Arid, it is an investigative matter. In the study, the epistemic basis is the historical materialistic dialectic, with observational and participant design, qualitative approach, involving bibliographical and empirical research; therefore, the last ones are documentary research and participant research. The documentary research occurs with social organizations, government federal and state agencies. Participant research occurs through participant observation, focus groups, and life histories. The field of study is the Brazilian Semi-arid, with cutouts in the Médio Sertão da Paraíba, specifically in the municipalities of Condado and São José do Sabugi, whose selection criterion was the identification of the management of P1MC, P1 + 2 and PCE by the same social regional organization. The study allowed an approximation of the semiarid, its contextualization on the planet and its cartographic movement in Brazil; an approach of the technologies, as an appropriation of the occupied space, seeking to investigate the internationalities that are lacking to reach the territories and readings that go back to the proposals of development support; an investigative analysis of contextualized educational practices in peasant territories and their possible strategies of coexistence with the semiarid. In the study, it was evidenced that contextualized educational practices for the coexistence with the Semi-Arid zone gain strength when they dialog with the environmental, cultural and territorial diversity; by promoting systematic dynamics experiences, providing the appropriation of good practices of coexistence with Semiarid by those who experience them; when investing in events with dialogic practices, such as exchange visits; by allowing the entrance of social technologies into the territory, as emancipatory territorialities, in order to strengthen organizational dynamics and networking processes.